EFEKTIVITAS PELAKSANAAN PENGGUNAAN ANGGARAN DANA DESA DALAM PROGRAM PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DI DESA GREGES, KECAMATAN TEMBARAK, KABUPATEN TEMANGGUNG TAHUN 2015-2018 - Lubherty Dewi Amalia; Sudati Nur Sarfiah; Gentur Jalunggono (DINAMIC : Directory Journal of Economic, 2019)
This study aims to determine and analyze the effectiveness of the use of Village Fund Budgeting in Greges Village, Tembarak District, Temanggung Regency in 2015-2018.The method used in this research is quantitative descriptive method. Primary data is obtained through filling out questionnaires and interviews. Secondary data was obtained from the report on the realization of the Village Fund budget in 2015-2018. The results showed that the implementation of the Village Fund in Greges Village, Tembarak District, Temanggung Regency had been running effectively based on the results of respondents' answers through questionnaires. Then the achievement of financial performance in implementing the Village Fund in development programs and empowerment programs from 2015-2018 experienced a fluctuating level of effectiveness. The factors that hinder the implementation of village funds are the low quality of human resources from government officials and the community, and the lack of community participation in the implementation of village funds so that village funds become less than optimal. Keywords:   Effectiveness,   Implementation,   Village   Funds,   Development   Programs,   Empowerment Programs